1987
DOI: 10.1149/1.2100594
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxidation and Redeposition Processes in Aqueous Alkali and Carbonate Solutions: II . Distinction Between Dissolution and Oxide Film Formation Processes

Abstract: The early stages of the process of anodic zinc oxidation in CO32-, SO42-, and C1-solutions around pH 11.5, were studied by cyclic voltammetry, as in part I. Unusual peak current dependence on sweep rate is observed at the first anodic peak (As). This behavior is explained in terms of a mixed process involving coupled diffusion and film formation. By correlating the shapes of peaks and peak potentials for different Zn surface preparations, and the relation of the peak current to sweep rate and to electrode rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 12 publications
2
37
0
2
Order By: Relevance
“…Although identification of these species is complex, these presumably arise from the reduction of two distinct Zn 2+ surface species. [26][27][28] Identical scans in which the only change was the removal of the 5000 s hold displayed only the peak at ∼-1.4 V SCE . Therefore, it is assumed that the peak at ∼-1.2 V SCE arose from a Zn 2+ surface species generated during the holding period.…”
Section: Resultsmentioning
confidence: 99%
“…Although identification of these species is complex, these presumably arise from the reduction of two distinct Zn 2+ surface species. [26][27][28] Identical scans in which the only change was the removal of the 5000 s hold displayed only the peak at ∼-1.4 V SCE . Therefore, it is assumed that the peak at ∼-1.2 V SCE arose from a Zn 2+ surface species generated during the holding period.…”
Section: Resultsmentioning
confidence: 99%
“…5(a) and (b). The obtained linear dependence between j pa v À1/2 and v 1/2 , with the intercept on the y-axis, suggests a mixed adsorption-diffusion control, i.e., j pa = k 1 v 1/2 + k 2 v [33]. The constant, k 1 was found to depend linearly on the concentration (k 1 (lA cm À2 V À1/2 s 1/2 ) = À0.08 + 1.27 · c, r 2 = 0.985), as expected from the Randles-Sevcik equation, and the appending diffusion coefficient D = 2.78 · 10 À6 cm 2 s À1 .…”
Section: Cyclic Voltammetrymentioning
confidence: 85%
“…[9][10][11] As shown in Fig. 1(b), two strong anodic current peaks were observed when the concentration of K 2 CO 3 was higher than 4.0 M, while the extent of anodic oxidation of Zn in 0.5-3.0 M K 2 CO 3 aqueous solutions were quite small.…”
Section: 1mentioning
confidence: 85%
“…3,6 There are few papers found that deals with the electrochemistry of Zn in carbonate aqueous electrolyte solutions. [9][10][11] Among them, redox behavior of Zn in concentrated carbonate system have not been reported. In this paper, Zn electrode behaviors in carbonate-based aqueous solutions (the aqueous solutions of K 2 CO 3 and concentrated K 2 CO 3 containing KOH) were examined.…”
Section: ¹mentioning
confidence: 99%